Development of the "Pangkatani" Scratch-Assisted Interactive Multimedia for Learning Exponents - Ahmad Akbar; Satya Santika; Mega Nur Prabawati (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Interactive multimedia has become a strategic need in mathematics teaching in the digital era, particularly for exponents, a topic still taught in conventional and abstract ways. This study developed and tested the feasibility of "Pangkatani," a Scratch-assisted interactive multimedia that integrates the local wisdom of cassava farming to give the concept of exponents a concrete context for ninth-grade students at SMPN 3 Sukahening. What makes Pangkatani distinctive is the way it combines visualization, interactive simulation, and culturally grounded gamification, which together are expected to raise student engagement, motivation, and conceptual understanding. The study used a Research and Development (R&D) approach with the ADDIE model and involved 19 students in a limited trial. The instruments were validation questionnaires for a media expert and a material expert, together with a student response questionnaire, analyzed through descriptive quantitative methods and supported by qualitative narrative. Media expert validation (90.77%) and material expert validation (95.38%) both fell in the "highly feasible" category, while the overall student response of 81.58% reflected gains in motivation, understanding, and willingness to learn. The findings suggest that embedding local wisdom in Scratch-based digital multimedia can strengthen contextual, constructivist, and meaningful mathematics learning. The Pangkatani model is recommended as a reference for developing similar media in other schools and as a contribution to the literature on culturally based educational multimedia. Further research with a wider scope and a longitudinal design is advised to test long-term effectiveness and replication.